Pemberdayaan Lansia Melalui Pendekatan Spiritual, Kesehatan, dan Sosial dalam Program Sekolah Lansia Berdaya - Habibi, Ibnu; Susanto, M. Arif; Ihwanuddin, Ihwanuddin; Zanki, Aulia Singa (Welfare : Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to empower elderly women in Kapas Village, Kapas District and Pohbogo Village, Balen District, Bojonegoro Regency through the Sekolah Lansia Berdaya activity. This activity was attended by 52 elderly participants (26 people from each village) and carried the theme "Happy Life in the Perspective of Islam". The main focus of the program is to increase the spiritual understanding of the elderly regarding the meaning of a happy life according to Islamic teachings, increase awareness of the importance of maintaining physical health, and strengthen the social role of the elderly in their surroundings. The method used is the Action Research method through a participatory action program approach. The results of the activity showed an increase in the spiritual aspect of the elderly, marked by a high spirit of worship and an attitude of gratitude. In addition, there was an increase in healthy living habits. The elderly also showed better self-confidence in interacting socially and participating in community activities. This activity succeeded in building awareness of the importance of a healthy and happy life based on Islamic values. This program successfully raised awareness about the importance of living a healthy and happy life in old age, based on Islamic values.